English: Bahasa Indonesia - Fajar Nur Rahmanni; Sumardiono Sumardiono (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2023)
This research was aimed at : (1) To find out the types of code mixing and code switching used in the Indonesian web series entitled “Layangan Putus” and (2) To find out the reasons of code mixing and code switching used in the Indonesian web series entitled “Layangan Putus”. This method used in this research is a descriptive qualitative method, which describes and analyzes the utterances consisting of code mixing and code switching along with the reasons taken from “Layangan Putus” series. The technique of collecting data in this research used non-participant observation and documentation which are in the form of words, phrases, and sentences. To analyze the data, the researcher used qualitative data analysis proposed by Miles and Huberman. The result of this research showed that there were: 170 utterances of code mixing, 246 utterances of code switching, and 74 utterances of reasons used by the characters. Those 170 utterances of code mixing, it had 95 of insertion, 44 utterances of alternation, and 31 utterances of congruent lexicalization. Those 246 utterances of code switching, it had 17 utterances of tag-switching, 173 utterances of intra-sentential switching, and 56 utterances of inter-sentential switching. Those 74 utterances of the reasons, it had 34 utterances of talking about particular topic, 9 utterances of be emphatic about something, 8 utterances of interjection, 9 utterances of repetition used for clarification, and 14 utterances of intention of clarifying the speech content for interlocutor. Based on the result of this research, it can be concluded that insertion type in code mixing, intra-sentential type in code switching, and talking about particular topic were the most dominant used by the characters in “Layangan Putus” series. Keywords: Code Mixing, Code Switching, Descriptive Qualitative Research